Āpana hate bāhire - Sinhā, Rājyeśvara (Yādabapura Biśvabidyālaẏa Prakāśanā, 2022)
Collection of articles on the role and association of Bengali Muslims in language and literature of early 20th century Bengal, India; previously published in various periodicals.
Includes index
Keywords: Bengali language; History.; Bengali literature; Muslim authors; History and criticism.; Periodical editors; India; Bengal.